TANGGUNGJAWAB BLU TRANSJAKARTA TERHADAP PIHAK KETIGA DALAM HAL TERJADI KECELAKAAN MENURUT UU NO. 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Elfrida R Gultom (Faculty of Law, Universitas Jenderal Soedirman, 2014)
The objective of Busway development is to provide transportation services faster, safer, comfortable, and affordable for people in Jakarta. Ticket prices are subsidized by the local government busway. Busway given special line, however could not be separated from the accident. In a carriage, in the event of an accident then apply provisions of Law No. 22 of 2009 on Traffic and Transportation. If there is a loss that hit the third party then setting responsibilities Public Service Agency TransJakarta Busway to third parties refer to the provisions of Article 194 paragraph (1) which determines that the public transport companies are not responsible for any losses suffered by third parties, unless the third party may prove that the loss is caused by the fault of public transport company. Under these provisions, if the third party wants to sue for damages, ketigalah party must prove the fault of the carrier, the claim is based on the basis of tort or on the basis of error set forth in Article 1365 of the Civil Code which stipulates that any action unlawfully harming others, require the person who carries the loss offset. Keywords: transport, the responsibility of the carrier, a third party, transport law